Design and architecture of wireless body area network using android application - Kumar Keshamoni (International Journal of Informatics and Communication Technology (IJ-ICT), 2019)
Patients in hospitals have issue with health instrumentality that's connected with wires to their body. Wired health instrumentality restricts the quality of the patient. Moreover, health caretaker’s area unit compelled to work the instrumentality and take the measurements. Hence, wireless observance of patient is incredibly effective resolution thereto drawback. The most target of this study was to analysis the present trend and prospect of wireless observance of patients within the hospitals. This study conjointly aims to create the epitome system to implement wireless observance. Additionally to that, this thesis conjointly studies most fitted technique for building the foremost effective wireless observance system. The sensing element nodes and receiver of the epitome were designed. Golem phone was used as entranceway to receive the information from sensing element node and forward the information into receiver. Bluetooth Low energy was wont to communicate between sensing element nodes and golem phone. LAN is employed to speak between golem phone and also the receiver that is connected to laptop. The sensing element readings were initially ascertained in Arduino Serial Monitor so sent to sink node. The sensing element readings of a body were displayed in golem phone and yet as within the web site. Real time information of sensing element was created and with success updated within the web site. The study of results and project showed that wireless observance would be terribly effective by exploitation Interference free, short vary and extremely secure suggests that of communication. Bluetooth low energy that is appropriate choice for the system. Style of sensing element nodes ought to be terribly tiny as a result of it's to be worn round the body. Therefore smaller parts ought to be used.